Teaching Performance of Physical Education Teachers in Primary Schools from the Perspective of the Theory of Interest - Ham, Ahmed Qasim Muhammed; Muhammed, Jahwar Khaleel; Ahmed, Nazik Sherzad; Adil, Nujan Heider (Journal of Duhok University, 2019)
The study aimed to identify the nature of teaching performance of physical education teachers according to the theory of interest, and the performance relation to the variables of age, gender, and the education directorate which the teacher belongs to. The sample consisted of 82 male and female teachers who were chosen from four directorates of education in Duhok governorate. The study depended on the Arabic version of the teacher’s interest list which was prepared by Gary and Martin (Gary D. Borich & Martin L. Tombari). After analyzing the data statistically, the results showed that the teachers of physical education have a great interest in all the dimensions that are found in the theory of interest. There are also statistical differences in the performance level which is attributed to two dimensions: First, the (self), and second, (educational achievement). There were no statistically significant differences in the level of performance which can be attributed to the variables of gender and the directorate of education. In light of the results, a number of recommendations and suggestions have been made.